Studies of P3HT:PCBM thin film formation for polymer solar cells / Mohd Nizam bin Yusli - Yusli, Mohd Nizam (2013)
Bulk heterojunction polymer solar cell is widely investigated throughout the decade. This is due to its potential as an alternative to inorganic solar cell such as silicon-base solar cell. Compared to inorganic solar cell, polymer solar cell is low in cost, much easier to fabricate and shows higher mechanical flexibility. Two types of conjugated polymers has been used in this study; [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) and poly(3-hexylthiophene) (P3HT). Many methods have been used to improve the efficiency of the solar cell. Thermal treatment on the organic layers has been utilized to increase the solar cell efficiency by improving the morphology and structure of the sample. It has been reported that by using different preparation methods, such as „slow grown‟ and „fast grown‟, the efficiency is enhanced. The morphology of the sample also varies when different solvent are used. In this study, we report the effect of thermal treatment on the optical, structural and morphological properties of the P3HT:PCBM blend thin films. The absorption, Raman, photoluminescence as well as x-ray diffraction spectra of the films will be discussed. The influence of thermal treatment on the performance of the P3HT:PCBM-based solar cells also investigated. The effect of solvent used also been discuss in this study. The polymer materials solutions were prepared using two types of solvents; 100% dichlorobenzene (DCB), 100% chloroform and 50%:50% mixture of DCB and chloroform. Then, the morphological characterizations of P3HT:PCBM bulk thin films were carried out by UV-Visible absorption spectroscopy, X-ray diffraction (XRD) spectroscopy, Atomic Force Microscopy (AFM) and Scanning electron microscopy (SEM). Furthermore, the P3HT:PCBM photoactive layer was sandwiched between two different electrodes of iv aluminum (Al) and indium tin oxide (ITO) to form the polymeric-based solar cells, namely ITO/P3HT:PCBM/Al devices. In this study it has been found that the thermal treatment process has a significant effect on the sample. Using different fabrication process also play a major role in improving the structure of the sample. Other than that, results of this study also indicate that solar cells employing the P3HT:PCBM bulk thin films prepared from the solvent mixture exhibit the enhanced fill factor and short-circuit current than that of other cells.